PETROCHEMICAL AND GEOCHEMICAL RESEARCHES OF GRANITOIDS OF THE ROS-TIKICH MEGABLOCK OF UKRAINIAN SHIELD WITH A VIEW TO CLARIFY THE ROCK'S COMPOSITION OF THEIR COMPLEXES - Kostenko, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The partition of the granitoids is carried out on the basis of studying laws of distribution of macro- and microelements in the rocks of the Ros-Tikich megablock of Ukrainian Shield. The selection of uman and gaysyn (in a large-sized variant) complexes is confirmed as independent subdivisions of correlation sсheme of Ukrainian NSK, and taking into account the results of geokhronology researches also and tetyev. At the same time, possibility of including of some petrotypes of gaysyn complex not is eliminated in the complement of fastov (as magmatic).